Modeling of fluid-particle interaction by coupling the discrete element method with a dynamic fluid mesh: Implications to suffusion in gap-graded soils. (August 2020) - Zhang, Fengshou; Wang, Tuo; Liu, Fang; Peng, Ming; Furtney, Jason; Zhang, Limin
Abstract: A new fluid–solid coupled numerical approach by combining the Dynamic Fluid Mesh method with DEM (discrete element method) is applied to simulate suffusion. The fluid mesh is generated according to the soil skeleton formed by coarse particles and updated at regular intervals. Seepage forces are calculated and applied on solid particles in the DEM model. The new approach accounts for permeability and porosity changes due to soil skeleton deformation and suffusion. A model of soil sample under triaxial stress condition is developed to simulate the suffusion process. The results show that the erosion process can be divided into three stages: initial stage when numerous fine particles are washed away and the flow rate increases with more eroded particles, deceleration stage when the erosion rate decreases and the flow rate tends to reach a steady state, and stabilization stage when the erosion rate levels off to zero gradually. Parametric studies show that the increase of hydraulic gradient and coarse particle size ratio both increase the eroded particle mass. However, high confining stress will decrease the eroded particle mass. Hydraulic gradient affects the whole process of suffusion whereas confining stress and particle size ratio mainly affect the second and third stages.